Review of 24 patients with Abdominal travma-induced colonicinjury - Hakan DEMİR and Zeki DÖŞEYEN and Yavuz ERYAVUZ and Sançar BAYAR and Hilmi KOCAOĞLU and Salim DEMİRCİ (Turkish Journal of Gastroenterology, 2019)
-